Quantum field theories in two dimensions collected works of Alexei Zamolodchikov - Zamolodchikov, Alexei (World Scientific, 2012)
A collection of reprinted works of Alexei Zamolodchikov who was a prominent theoretical physicist of his time. It contains his works on conformal field theories, 2D quantum gravity, and Liouville theory. It also includes Alexei Zamolodchikov's works on non-perturbative methods in 2D quantum field theory, and on integrable models.